Spiritual Activism as a Means for Social Transformation: Womanist and Chicana Feminist Possibilities. Issue 3 (2nd July 2020) - Salazar Pérez, Michelle; Saavedra, Cinthya M.
ABSTRACT: In the wake of Trump's presidency, children of color have been increasingly subjected to overt racism in and outside of educational settings. After seeing "In light of the Trump effect" or the anxiety and fear that has ensued for children of color since Trump's pre-election campaign, we suggest that concerted actions are needed from often untapped sources that cross human-centric boundaries such as spiritual activism. We contend that we must rethink human-more-than-human binaries, while simultaneously working towards equity and social justice. Womanist and Chicana feminist spirituality de-centers the human, while providing a means to transform oppressive conditions. In this theoretical wondering, we posit that spiritual activism is vital to the well-being of young children of color and the broader world.